2020
DOI: 10.1007/s11914-020-00638-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Lowering Drugs and Fracture Risk—a Systematic Review

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 110 publications
(121 reference statements)
2
17
0
Order By: Relevance
“…Among other anti-diabetic drugs evaluated, metformin, voglibose, and insulin showed benefits, whereas nateglinide raised the risk of fracture. Several recent studies have indicated that metformin is associated with a reduced risk of fracture ( 36 , 42 , 43 ), while previous studies have reported an increased risk of falling among patients using insulin ( 12 ). Therefore, metformin could be considered in patients susceptible to fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Among other anti-diabetic drugs evaluated, metformin, voglibose, and insulin showed benefits, whereas nateglinide raised the risk of fracture. Several recent studies have indicated that metformin is associated with a reduced risk of fracture ( 36 , 42 , 43 ), while previous studies have reported an increased risk of falling among patients using insulin ( 12 ). Therefore, metformin could be considered in patients susceptible to fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs are used in the treatment for T2D, but only glitazone (which was not used by any of the participants in the present study) shows detrimental effects, whereas it is controversial whether other antidiabetic drugs influence fracture risk, bone density, or bone turnover ( 32 ). Metformin has in a randomized controlled trial been shown to reduce bone turnover markers ( 33 ), whereas observational studies in general report either beneficial or neutral effects of metformin on fractures or BMD ( 32 , 34 ). Sulfonylurea and insulin do not change bone turnover ( 32 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sulfonylurea and insulin do not change bone turnover ( 32 , 35 ). The effect of these drugs on fracture risk is controversial as both drugs have been linked to an increased fracture risk through an increased risk of hypoglycemia, however, observational studies report neutral or even protective effects of the treatments ( 34 ). DPP-IV and GLP-1 receptor agonist have in preclinical studies shown bone formative effects ( 32 ), but observational and randomized controlled trials showed neutral effects on fracture risk ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mice in the liraglutide treatment groups suffered greater weight loss than the T1D mice which might cause negative effect on bone, which might partly explain the only partial improvement of bone microarchitectures. Metformin was also found to have an effect on bone metabolism, which was also mainly associated with neutral outcomes or decreased fracture risk in comparison to treatment with other glucose-lowering drugs ( 10 ). Metformin was found to decrease ALP, CTX-1, TRACP 5b, PINP, and RANKL, but increase OPG, RUNX2, and OPG/RANKL ratio in diabetic rat, indicating a bone protection role ( 40 ), but it was not exactly the same as liraglutide.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1R agonists also exert protective effects on bone tissue in vitro and in vivo (7)(8)(9). Some clinical studies have found neutral effects of liragutide on bone, but there was also a few meta-analysis of 16-59 randomized controlled trials with 11,206-49,602 patients with T2DM which showed that compared with placebo and other antidiabetic drugs, liraglutide was associated with a significant reduction in the risk of bone fractures (10)(11)(12)(13). However, clinical and experimental research data in the context of T1D are scarce.…”
Section: Introductionmentioning
confidence: 99%